Simulation of Ethanol and Acetone Extraction from Aqueous Solutions in Membrane Contactors - Reza Sohrabi, Mahmoud; Marjani, Azam; Shirazian, Saeed; Moradi, Sadegh (Asian Journal of Chemistry, 2011)
In this work a 2D mathematical model was developed to study liquid extraction by membrane contactors. The equations of model were solved by numerical method based on finite element method. The system studied in this work is a hollow-fiber membrane based extractor using near-critical carbon dioxide. Simulations results were compared with the experimental data and showed good agreement. This mass transfer model is more accurate than other models and represents a general approach which can be applied in other membrane separation.